PROPORTION OF TARGET AND NON TARGET SPECIES IN SELECTED MESH SIZES OF GILLNET FISHERY ALONG MUMBAI COAST OF MAHARASHTRA - SHABIR A. DAR; SALY N. THOMAS (The Bioscan, 2015)
The present study on the proportion of target and non target catch in gillnet fishery from three sectors of gillnetters viz., inboard motor (IBM), outboard motor (OBM) and non-motorised gillnetter was conducted during Decem- ber 2010 - November 2011 at Cuff Parade, Versova and Mahim of Mumbai coast respectively. Altogether six non target species in mesh size (12 and 14 mm), 23 species in mesh size (48 and 50 mm) and 18 species in mesh size (32 and 34 mm) were caught in selected mesh sizes targeted for white sardine (Esculosa thoracata), oil sardine (Sardinella longiceps) and catfish (Arius spp.) in OBM, IBM and non motorised gillnetters respectively. It was found that maximum target catch was observed in mesh sizes of 32 and 34 mm operated for Sardinella longiceps (oil sardine) fishery, while least was found in mesh size of 48 and 50 mm operated targeting Arius species.